2023
DOI: 10.1021/acscatal.2c06054
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Alkylation of Unactivated C–O Bond: Solvent Molecule Affects Competing β-H Elimination and Reductive Elimination Dynamics

Abstract: Despite the fact that metal-catalyzed asymmetric alkylative cross-couplings have been well-established, enantioselective alkylative substitution of an unactivated C–O bond remains a challenge due to the lack of strategies to cleave the C–O bond and suppress β-H elimination as well as control stereochemistry simultaneously. Herein, the enantioselective alkylative activation of an unactivated C–O bond with β-H-containing alkylating reagents was described using a chiral nickel catalyst, and versatile axially chir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…This transformation was carried out in the presence of L3 as the ligand and MgI 2 as the additive, using THF as the solvent at 45 °C (Scheme 12). [25] Control experiments revealed that the transformations were equally efficient without the presence of inorganic salts MgI 2 , ruling out its role in suppressing β‐H elimination. These control experiments highlighted the crucial role of the solvent THF in facilitating these transformations.…”
Section: Metal Catalyzed Ring‐opening Of Benzofuranmentioning
confidence: 98%
“…This transformation was carried out in the presence of L3 as the ligand and MgI 2 as the additive, using THF as the solvent at 45 °C (Scheme 12). [25] Control experiments revealed that the transformations were equally efficient without the presence of inorganic salts MgI 2 , ruling out its role in suppressing β‐H elimination. These control experiments highlighted the crucial role of the solvent THF in facilitating these transformations.…”
Section: Metal Catalyzed Ring‐opening Of Benzofuranmentioning
confidence: 98%
“…The catalytically active species in the arylation is the mono‐ligated nickel, while catalytically active species in the alkylation is the bis‐ligated nickel. The same group also developed similar strategies to suppress β ‐H elimination in alkylative cross‐couplings via the unique solvent effect of tetrahydrofuran [38] . Recently, Gu, Shi, Deng, and co‐workers developed a regioselective C(sp 2 )−O bond activation method for C−N atropisomer synthesis (Scheme 8b) [39] .…”
Section: Five‐membered Bridged Substratesmentioning
confidence: 99%
“…The same group also developed similar strategies to suppress β-H elimination in alkylative cross-couplings via the unique solvent effect of tetrahydrofuran. [38] Recently, Gu, Shi, Deng, and co-workers developed a regioselective C(sp 2 )À O bond activation method for CÀ N atropisomer synthesis (Scheme 8b). [39] The high regioselectivity benefits from the high stability of the in situ formed (amido)ethenolate via oxidative addition.…”
Section: Bridged Substrates With O As Linking Atommentioning
confidence: 99%
“…12 Very recently, the Cao group developed the asymmetric version of this transformation using ring strained dibenzofurans at 25 °C to 60 °C. 13 It is worth highlighting that the above examples represent the breakthroughs within this domain. However, the ring opening of dibenzofurans and the subsequent formation of C–O, C–N, and C–P bonds are still limited.…”
Section: Introductionmentioning
confidence: 99%